2021
DOI: 10.1109/tuffc.2021.3077704
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ultrasound Biofilm Ablation: Investigation of Histotripsy for the Treatment of Catheter-Associated Urinary Tract Infections (CAUTIs)

Abstract: Urinary catheters often become contaminated with biofilms, resulting in catheter-associated urinary tract infections (CAUTIs) that adversely affect patient outcomes. Histotripsy is a non-invasive focused ultrasound therapy previously developed for the non-invasive ablation of cancerous tumors and soft tissues. Histotripsy has also previously shown the ability to treat biofilms on glass slides and surgical meshes. Here, we investigate the potential of histotripsy for the treatment of CAUTIs for the first time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 53 publications
0
21
1
Order By: Relevance
“…Histotripsy can therefore ablate three-dimensional volumes of any required size and shape by translating the focal zone, as determined by the diffraction pattern of the array, through a predetermined volume. Due to these features, histotripsy is currently being developed for many clinical applications including the treatment of kidney stones (Duryea et al 2011), benign prostatic hyperplasia (Hempel et al 2011, Roberts et al 2014, Schuster et al 2018, deep vein thrombosis (Maxwell et al 2011a, Zhang et al 2015, Goudot et al 2019, Bader et al 2021, congenital heart disease (Xu et al 2010, Owens et al 2011, Miller et al 2013, biofilm ablation (Xu et al 2012, Bigelow et al 2018, Childers et al 2021, and cancer (Vlaisavljevich et al 2013b, 2016b, Brisbane et al 2017, Smolock et al 2018, Longo et al 2019, Schade et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Histotripsy can therefore ablate three-dimensional volumes of any required size and shape by translating the focal zone, as determined by the diffraction pattern of the array, through a predetermined volume. Due to these features, histotripsy is currently being developed for many clinical applications including the treatment of kidney stones (Duryea et al 2011), benign prostatic hyperplasia (Hempel et al 2011, Roberts et al 2014, Schuster et al 2018, deep vein thrombosis (Maxwell et al 2011a, Zhang et al 2015, Goudot et al 2019, Bader et al 2021, congenital heart disease (Xu et al 2010, Owens et al 2011, Miller et al 2013, biofilm ablation (Xu et al 2012, Bigelow et al 2018, Childers et al 2021, and cancer (Vlaisavljevich et al 2013b, 2016b, Brisbane et al 2017, Smolock et al 2018, Longo et al 2019, Schade et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, tissue can be homogenized into components at a subcellular level. Such an effect can be employed to liquefy blood clots from cardiovascular events (Maxwell et al 2009, Burgess et al 2012, destroy tumors (Vlaisavljevich et al 2013a, Vidal-Jove et al 2022, kill bacteria (Bigelow et al 2009, Childers et al 2021, Matula et al 2021, and structurally modify tissue to address congenital anomalies (Owens et al 2009, Maxwell et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to eukaryotic tissues such as tumors, studies have shown that histotripsy will disrupt bacterial biofilms on surgical meshes, microscope slides, and graphic discs [22][23][24][25][26]. More recently, our lab showed that conventional histotripsy methods could be used to precisely target the lumen of urinary catheters, remove luminal biofilms, and kill suspended bacteria [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our team conducted a study investigating histotripsy for the treatment of luminal biofilms [ 15 ]. Histotripsy is an image-guided and nonthermal focused ultrasound ablation method that uses high-pressure acoustic pulses to noninvasively ablate biofilms and tissues through acoustic cavitation [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation